Only severe Injuries are effectively reduced by muscles' injury prevention protocols in football players: A systematic review [version 2; peer review: 2 approved] - Amani Kacem; Iheb Belhadj Youssef; Sana Bhiri; Marwa Ghanmi; Rihab Moncer; Sinen Frigui; Dhekra Chebil; walid Ouannes; Sonia Jemni; Sahbi Mtaouaa; Sana Salah (F1000Research)
Background Muscle injuries are the most frequent in football and may lead to the end of a player’s career. Many studies have evaluated the effectiveness of prevention programs for all injury types. Few studies have evaluated the effects of exercise on muscle injuries. The aim of this study is to report, through a systematic review of research of high level of proof (randomized controlled trial) the efficacy of preventive programs for muscle injuries for football players. Methods A documentary search was conducted in October 2022 from three databases: Medline via its PubMed interface, Google Scholar, and COCHRANE databases. We only included original articles published between October 2012 and October 2022 with a high level of evidence. The research was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria. The target population consisted of professional and semi-professional footballers. The intervention in question was structured injury preventive protocols, including specific training or pre-established protocols such as the FIFA 11+ program, compared to each other or with regular training sessions. The main outcomes were the incidence rates of muscle injuries and severe injury in each group, as well as the time loss to injury. Results Seven randomized controlled trials with a high level of evidence confirmed using the PEDRO scale were included. There were 3815 male professional football players. There was heterogeneity in the age, hours of exposure, and duration of the intervention. The prevention protocols used were FIFA 11+, bounding exercises, NHE, and stretching exercises. Structured exercises significantly reduce the severity of muscle injury and, consequently, time loss to injury. Discussion Despite the diversity of prevention programs, teams still lack standardized programs. Structured exercises, such as FIFA 11+ and bounding exercises, which combine strengthening, body kinesthesic awareness, and neuromuscular control, reduce the incidence and severity of muscle injury. FIFA 11+ is the first and most complete structured program, but lacks some exercises, such as adductor strengthening. Conclusion This review showed the interest in structured exercises in reducing severity and time loss to injury in professional football players. It shows that effective MI prevention program should combine variable structured programs taking into consideration risk evaluation. Registration This review was registered on 8/17/2023 in the International Prospective Register of Systematic Reviews under the reference code CRD42023452202.